2022
DOI: 10.1039/d1nr06143g
|View full text |Cite
|
Sign up to set email alerts
|

Nanoengineered myogenic scaffolds for skeletal muscle tissue engineering

Abstract: Here, we developed a nano-engineered biomaterial optimized for skeletal muscle proliferation and differentiation. Nanoclay disks were used to control the release of insulin-like growth factor (IGF-1), a key myogenic and immunogenic regulator.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 50 publications
1
24
0
Order By: Relevance
“…Nanoclays are silicate-derived multilayers that have been shown to play a key role in the physiology of a wide range of tissues such as bone [48]. Several studies have proved that these nanoparticles are able to complement the already adequate properties of gelatin hydrogels for bone tissue regeneration [16,[49][50][51]. One of the main advantages of nanoclays consists in improving the gelatin's poor mechanical properties.…”
Section: Bioprintingmentioning
confidence: 99%
“…Nanoclays are silicate-derived multilayers that have been shown to play a key role in the physiology of a wide range of tissues such as bone [48]. Several studies have proved that these nanoparticles are able to complement the already adequate properties of gelatin hydrogels for bone tissue regeneration [16,[49][50][51]. One of the main advantages of nanoclays consists in improving the gelatin's poor mechanical properties.…”
Section: Bioprintingmentioning
confidence: 99%
“…Calibration curve was designed at + 0.6 V from the concentration of acetylcholine and observed to be linear [R 2 = 0.7528, SD = 12.35, RSD = 49.05 %, error bar = 10.0 %, and n = 9] (Figure 8b). Analytical parameters of the prepared sensor [Sensitivity (101.27 nAÎŒM À 1 cm À 2 ), low LOD to ∌ 11.58 pM and LOQ (38.60 pM)] were calculated using the equations (6)(7)(8). Here, m represents the slope of the calibration curve (y = 0.0032 x + 21.172), A represents the active surface area (0.0316 cm 2 ) of the provided electrodes and SD represents the standard deviation (12.35 ÎŒA) of acetylcholine concentration in the calibrated potential of + 0.6 V. [28] The linear dynamic range (100 pM ∌ 100 ÎŒM) and linearity (R 2 = 0.9520) following an equation, y = 2.1163x + 21.745, was also found from the calibration curve (Figure 8c).…”
Section: Acetylcholine Detection With Gce/v 2 O 5 Nrs/bpm Sensormentioning
confidence: 99%
“…[3][4][5] In the previous studies, it was reported that bio-molecules could be determined by using different experimental methods such as Capillary Electrophoresis, Chemiluminescence, Electrochemical Analysis, Fluorescence Analytical Procedure, High-Performance Liquid Chromatography, High Performance Liquid Chromatography Mass Spectrometry, Liquid Chromatography Tandem Mass Spectrometry, Paper Spray Mass Spectrometry, Spectro-photometry, Surface Plasmon Resonance, Thin Layer Chromatography and ultraviolet-visible spectro-photometry. [6][7][8][9][10][11] A sensor is an investigative instrument that combines an element with a physicochemical transducer to recognize a particular component. A transducer converts the emerging indication from the analyte's interaction with the element into a quantitative signal (voltage and current) that may be easily quantified.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We hence choose ADSCs as parent cells to produce exosomes, and investigate the effects of ADSCs exosomes on microtia chondrocytes as well as the underlying mechanism of action. With excellent mechanical properties, superior biocompatibility, antibacterial ability and bioactivity, Gelma hydrogel has been widely applied to the field of 3D culture [ 26 ] and controlled delivery of bioactive factors [ 27 ]. The porous Gelma with reticular pores size of 100 to 200 ÎŒm could be favorable to promote ADSCs adhesion/proliferation and nutrients transferring.…”
Section: Introductionmentioning
confidence: 99%